2007
DOI: 10.1093/rheumatology/kem075
|View full text |Cite
|
Sign up to set email alerts
|

Long-term infliximab treatment in rheumatoid arthritis: subsequent outcome of initial responders

Abstract: This study of patients treated in clinical practice with infliximab demonstrated that secondary non-response occurred in around half the patients in the first year. The data highlight the need to continue development of other therapies as well as investigation of the underlying causes of this loss of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 9 publications
3
45
2
3
Order By: Relevance
“…In observational studies, continuation rates are usually lower than in clinical randomized trials, 66% of the patients continued infliximab infusions after one year [8] and after two years' intervention 67% [9] and 73% [10] drug survival rates were reported. In the study of Buch et al, only 27 out of 174 patients (16%) continued infliximab treatment at the 24 months' time-point [14]. In the present study, 40% of the patients continued with infliximab treatment after the two years' follow-up 13 since they had achieved at least a 50% response without any severe adverse event or other reason requiring discontinuation of the treatment.…”
Section: Other Adverse Eventscontrasting
confidence: 40%
See 3 more Smart Citations
“…In observational studies, continuation rates are usually lower than in clinical randomized trials, 66% of the patients continued infliximab infusions after one year [8] and after two years' intervention 67% [9] and 73% [10] drug survival rates were reported. In the study of Buch et al, only 27 out of 174 patients (16%) continued infliximab treatment at the 24 months' time-point [14]. In the present study, 40% of the patients continued with infliximab treatment after the two years' follow-up 13 since they had achieved at least a 50% response without any severe adverse event or other reason requiring discontinuation of the treatment.…”
Section: Other Adverse Eventscontrasting
confidence: 40%
“…According to the patients' records, 6 / 23 patients discontinued the treatment due to inadequate response during the first seven months, and 17 / 23 patients had an appropriate response at the beginning but discontinued the treatment later because of waning efficacy. Buch et al reported also that some patients could not maintain an already achieved response at later time points [14]. In observational studies, the rate of discontinuation due to inefficacy varies between 9.2-11% [8, 10,16].…”
Section: Other Adverse Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite the undoubted success of anti-TNFα, only a quarter of patients treated with a combination of a TNFα inhibitor plus methotrexate achieve disease remission (defined as a DAS-28 score of less than 2.6). In addition, up to 50% of primary responders lose their response within 12 months of the start of therapy (Buch et al, 2007). Hence, there remains a need for more effective anti-arthritic medicines.…”
Section: Overview Of Ramentioning
confidence: 99%